Hydroxysafflor yellow A promotes osteogenesis and bone development via epigenetically regulating β-catenin and prevents ovariectomy-induced bone loss. (August 2021) - Wang, Peng; Wang, Min; Zhuo, Tingling; Li, Ying; Lin, Weiping; Ding, Lingli; Zhang, Meng; Zhou, Chi; Zhang, Jinfang; Li, Gang; Wang, Haibin; Xu, Liangliang
Graphical abstract: Abstract: In clinical treatment, there is increasingly prevalent that traditional Chinese medicine treats common bone diseases including osteoporosis. Hydroxysafflor yellow A (HSYA), one of the essential compounds of Safflower, has been used as the therapy for thrombus, myocardial ischemia, and inflammation, but its effect on osteogenesis through epigenetic control and ovariectomy-induced bone loss in vivo has not been explored. Therefore, the study aimed to explore the function and mechanism of HSYA on bone formation and development. We found HSYA could enhance the cell viability and promote osteogenesis of hBMSCs in vitro. Mechanistically, HSYA could increase the expression of β-catenin leading to its accumulation in the nucleus and activation of downstream targets to promote osteogenesis. Besides, RNA-seq and quantitative RT-PCR and western blot showed KDM7A was significantly increased by HSYA. The occupancy of H3K27me2 on β-catenin promoter was significantly decreased by HSYA, which could be reversed by silencing endogenous KDM7A. More importantly, HSYA promoted bone development in chick embryos and prevented ovariectomy (OVX)-induced bone loss in SD rats. Taken together, our study has shown convincing evidence that HSYA could promote osteogenesis and bone development via epigenetically regulating β-catenin and prevent ovariectomy-induced bone loss.